Efeitos do treino de cuidadores sobre comportamentos de apoio à adesão às orientações nutricionais por portadores de diabetes - MALCHER, Michele da Silva (Universidade Federal do Pará, 2011)
Health studies have pointed out that social support is one of the factors related to the adherence to diabetes patients treatment. Based on behavior analysis reference and especially on Goldiamonds constructional approach this study aimed to evaluate the effects of training procedure on caregivers support behavior offered to adult patients feeding behavior. Further, it was intended to analyze effects of this training on the patients adherence to dietary prescription. Taking part on this study were three women enrolled in a program for diabetes patients and one family member of each patient, amounting to three caregiver-patient dyads, two of which were allocated on a Training Condition (TC) and one, on a Non-Training Condition (NTC). As information sources, one used the verbal reports of the patients and of the caregivers, direct observation of behavioral interaction and clinical indicators. Using the subject as its own control, the intervention consisted on the training in contingency analysis and behavioral handling, accomplished in home visits by means of self monitoring records. The results showed that caregivers who took part on the Training Condition presented enlargement on the support behavior repertoire, which was not verified regarding the caregiver who took part on the Non-Training Condition. The glycemic levels reduction and the reports presented by the Training Condition patients suggest that the intervention has contributed to improvements on the adherence to nutritional orientations by theses patients.